(untitled) (Al-Qamar, 2018)
The tendency of Said Nursi towards politics became evident when he started criticizing the views of British officials and even some Muslims against Holy Quran. He started a movement for the awareness of magnificence of Holy Quran and made impressive speeches on every important public event. He declared the divine book as a source of all wisdom which not only defines philosophy of natural phenomena but also unity and progress of nations. He was delighted of the movements of Syed Jamal-u-Din Afghani and Namiq Kamal. On account of his struggle to promote Islamic views and writing a great Tafseer of Quran, he was sent to madhouse and then to a secret prison by Sultan Abdul Hameed. When the British court took his trial as a rebellion, instead of apologizing, he faced it bravely and defended the claim which to his discharge.